Unusual importance of insectivory in the diet of the Neotropical otter, Lontra annectens (Major, 1897) (Mammalia, Carnivora) - Luis Ángel Pozos-López; Noé González-Ruiz; José Ramírez-Pulido (Neotropical Biology and Conservation)
The Neotropical otter, Lontra annectens, is a predator specialized in aquatic prey, and the main diet of this otter is fish, supplemented mainly by crustaceans and opportunistically by mollusks, insects, and vertebrates such as mammals, amphibians, birds, and reptiles. Occasionally, they eat fruits. This study was conducted on the El Despoblado River near Villa Comaltitlán, in southern Chiapas. We carried out monthly visits along the riverbanks to collect otter scats from April 2018 to April 2019 and found that insects make up more than half of the diet of otters living in this river. Although insects are a common food in the diet of Neotropical otters, the abundant presence of hellgrammites (dobsonfly larvae; Insecta, Megaloptera) had not been recorded before. Otters were found to consume hellgrammites, which are abundant, easy to catch, and have a high nutritional value. This is probably due to the scarce availability of fish and crustaceans in this part of Chiapas.